SISTEM PAKAR MENDIAGNOSA PENYAKIT GIGI MENGGUNAKAN METODE CERTAINTY FACTOR - Siti Zaharah; Katen Lumbanbatu (STMIK KAPUTAMA, 2020)
Expert system is a computer-based application that is used to solve problems as thought by experts. One problem that can be solved by using an expert system is diagnosing.Teeth are one of the most important organs in the human body. As the only organ that cannot heal itself, the tooth becomes an organ that is highly maintained and cared for during one's life. The teeth are also very important organs in the food processing process. In this study the user chose one of three types of dental disease as their assumptions including periodontitis, gingivitis and dental caries. The system will give questions about the symptoms of dental disease. The certainty factor value of the three types of dental diseases based on user input is 95.9% of gingivitis, 92.7% of periodontitis and 85.9% of dental caries. So it can be concluded that the calculation results indicate the likelihood of users suffering from gingivitis 95.9%. Henceforth the system will provide a handling solution.